THE ROLE OF PHYSICAL ACTIVITY IN DEVELOPING STUDENTS' SOCIAL WELL-BEING - Brodowska- Szewczuk, Jolanta (Management and Administration Journal, 2025)
Health Literacy, or health awareness, is an essential competency for individuals in the 21st century. It enables the understanding of the purpose of preventive, diagnostic, and therapeutic actions, which translates into greater control over one's health. Taking care of personal health awareness is an investment in health that benefits both individuals and society as a whole. Therefore, studying health literacy among students, who are responsible for their own lives and will also influencethe lives of others, is an important topic. The article aims to analyze global research on the topic of Health Literacy among students. The reviewed studies provide strong evidence of the relationship between health literacy and factors such as age, semester of study, gender, field of study, parental education, and socioeconomic status. Other potential determinants may include access to information, health-related experiences, financial situation, and social support. Limited health literacy poses a significant challenge to health policy and education worldwide, albeit to varying degrees in different countries. Research should draw conclusions about which groups require systemic support to enhance their health literacy.